Psychological Approach of Jadis’ Act of Violence in Novel Entitled Narnia: The Lion, The Witch, and The Wardrobe by C.S. Lewis - Grifian Azharinas; Bunayya Izzani; Wahyu Indah Mala Rohmana (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This article presents a psychological analysis of Jadis, the White Witch, a character in the novel